The effect of long-term management ofnative grass pastures on steer gains - F.K. Brazle; Dale L. Lanham; Jeffrey L. Davidson (Kansas Agricultural Experiment Station Research Reports, 2000)
Three hundred thirteen mixed breed steers (558 lb) were used to determine the effect of long-term management of native grass pastures on gain. Steers were allotted randomly to eight pastures previously grazed for 1/2 season (1 steer/2 acres from April to July 15, 81 days) or 3/4 season (1 steer/3 acres from April to August 15, 112 days) from 1990 to 1998. In 1999, all pastures were stocked at 1 steer/2 acres and grazed 83 days until July 15 or 16. The steers received free-choice mineral and were supplemented six times with 2 lb of 20% crude protein range cubes to aid in gathering. The steers on pastures previously grazed for 3/4 season gained faster (P<.01) than those on pastures previously grazed for 1/2 season. The 1/2-season pastures appeared to have taller, more mature grass left after the 1999 grazing season than those previously grazed for 3/4 season. The 1999 season was extremely wet until July 15, which may have been a factor in the gain difference. This study clearly showed that gains were good following either system of grazing. However, under these environmental conditions, pastures previously grazed for 3/4 season had the advantage.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Stocker cattle; Grazing cattle; Native grass